Electron Emission Suppression from Cathode Surfaces of a Rod-Pinch Diode - 高屹 尹佳辉 孙剑锋 张众 张鹏飞 苏兆锋 (Chinese physics letters, 2010)
The theory and method of suppressing electron emission from cathode surfaces is introduced, including increasing the emission threshold, reducing the surface electric field and shielding the emitted electrons. The stainless steel-graphite and Teflon-graphite composite cathodes are designed to test the above methods for a rod-pinch diode. The experiments are performed on the inductive voltage adder, and the results indicate that the Teflon-graphite composite cathode is effective in suppressing electron emission from the specified cathode surface, while the stainless steel-graphite composite cathode fails. The reasons are analyzed theoretically.